Faits divers – inforozrywka w prasie - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The article has been dedicated to profile of the press texts’ specific group called fails divers. According to the author they may be considered as an example of linking information to an entertainment. Owing to them we obtain a piece of information that is not as essential as incredible, the reading provides us firstly with an entertainment. Because of this it may be improper to consider fails divers as a specific variety of a press note. However, formal determinants do not supply a base sufficient to define faits divers as a separate informative species. Faits divers are hybrid product, which attraction and easy receipt have come into contemporary fashion of popular informative species.